Commodification and Commercialization of Islamic Da'wah Practice on Indonesian Television - Aang Ridwan (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2019)
This study aims to understand and analyze the relationship between da'wah's practice, especially in the form of Islamic broadcasting on television media, and the presence of popular culture in society. This research is qualitative research using descriptive and holistic research methods. Data collection was carried out through interviews, observation, and documentation techniques. Besides, researchers also use critical discourse analysis methods as data analysis methods. The use of analytical techniques that combines various approaches in critical discourse analysis, such as textual analysis, sociological macro analysis, as well as the use of ideological and power relations theories, is assumed to be the right technique in formulating meaning and understanding the practice of da'wah on television more critically. This research wants to answer how the construct of da'wah practice on television and the role of television media in the commodification and commercialization of Islamic da'wah from the perspective of critical discourse analysis. Penelitian ini bertujuan untuk memahami dan menganalisis bagaimana relasi antara praktik dakwah, terutama dalam bentuk penyiaran Islam di media televisi, dengan kehadiran budaya populer di masyarakat. Penelitian ini adalah penelitian kualitatif dengan metode penelitian deskriptif dan holistic. Pengumpulan data dilakukan melalui wawancara, observasi dan dokumentasi. Selain itu, peneliti juga menggunakan metode analisis wacana kritis sebagai metode analisa datanya. Penggunaan teknik analisa dilakukan untuk analisis tekstual, analisis makro sosiologis, juga penggunaan teori ideologi dan relasi kuasa, diasumsikan sebagai teknik yang tepat dalam merumuskan makna dan memahami praktik dakwah di televisi secara lebih kritis. Penelitian ingin menjawab bagaimana konstruk praktik dakwah di televisi dan peran media televisi dalam hal komodifikasi dan komersialisasi dakwah Islam dalamperspektif analisis wacana kritis.